Preparation of Superhydrophobic P-TiO2-SiO2/HDTMS Self-Cleaning Coatings with UV-Aging Resistance by Acid Precipitation Method - Le Zhang; Ying Liu; Xuefeng Bai; Hao Ding; Xuan Wang; Daimei Chen; Yihe Zhang (Nanomaterials)
The superhydrophobic coatings for outdoor use need to be exposed to sunlight for a long time; therefore, their UV-aging resistances are crucial in practical applications. In this study, the primary product of titanium dioxide (P-TiO2) was used as the raw material. Nano-silica (SiO2) was coated onto the surface of P-TiO2 by the acid precipitation method to prepare P-TiO2-SiO2 composite particles. Then, they were modified and sprayed simply to obtain a superhydrophobic P-TiO2-SiO2/HDTMS coating. The results indicated that amorphous nano-SiO2 was coated on the P-TiO2 surface, forming a micro–nano binary structure, which was the essential structure to form superhydrophobic coatings. Additionally, the UV-aging property of P-TiO2 was significantly enhanced after being coated with SiO2. After continuous UV irradiation for 30 days, the color difference (ΔE*) and yellowing index (Δb*) values of the coating prepared with P-TiO2-SiO2 increased from 0 to 0.75 and 0.23, respectively. In contrast, the ΔE* and Δb* of the coating prepared with P-TiO2 increased from 0 to 1.68 and 0.74, respectively. It was clear that the yellowing degree of the P-TiO2-SiO2 coating was lower than that of P-TiO2, and its UV-aging resistance was significantly improved. After modification with HDTMS, the P-TiO2-SiO2 coating formed a superhydrophobic P-TiO2-SiO2/HDTMS coating. The water contact angle (WCA) and water slide angle (WSA) on the surface of the coating were 154.9° and 1.3°, respectively. Furthermore, the coating demonstrated excellent UV-aging resistance. After continuous UV irradiation for 45 days, the WCA on the coating surface remained above 150°. Under the same conditions, the WCAs of the P-TiO2/HDTMS coating decreased from more than 150° to 15.3°. This indicated that the retention of surface hydrophobicity of the P-TiO2-SiO2/HDTMS coating was longer than that of P-TiO2/HDTMS, and the P-TiO2-SiO2/HDTMS coating’s UV-aging resistance was greater. The superhydrophobic P-TiO2-SiO2/HDTMS self-cleaning coating reported in this study exhibited outstanding UV-aging resistance, and it had the potential for long-term outdoor use.